Methodological approach to conducting a comparative analysis of economic systems at various stages of historical development - F. P. Volkov; E. V. Kulyasova; A. V. Voronin (Вестник университета, 2023)
Comparative studies of economic systems have been gaining popularity in recent years. The existing methodology for comparing quantitative indicators of the functioning of the economies of different countries has a number of limitations. The presented article discusses methods for comparing the purchasing power of monetary units of the economies of different countries, and also analyzes the possibility of using them to carry out a comparative analysis of economic indicators and indicators of the development of industries in the USSR and modern Russia in order to develop proposals for improving the state economic and industrial policy. The analysis of methods of comparing the purchasing power of monetary units made it possible to substantiate the choice of approaches for comparing production, technological and financial and economic indicators of the development of industries in the USSR and the Russian Federation. Based on the selected approaches of comparing monetary units, the conversion coefficients for various historical periods were calculated: the USSR (from 1940 to 1990) and the Russian Federation (from 2000 to 2020).